Pengenalan Permainan Tradisional Bali Dolanan Bagi Anak Usia Dini - Arini, Ni Putu Sri; Gede Anadhi, I Made; Komang Sindu Putra, Ida Bagus (Generasi Emas, 2024)
The aim of this research is to reintroduce the traditional Balinese game dolanan, whose existence needs to be maintained so that it is not eroded by the era that is starting to be touched by modern culture. The type of research used is literature review research with a focus on the traditional Balinese game "Dolanan". The data sources obtained are based on the results of identification, evaluation and synthesis of research work produced by practitioners and previous researchers such as articles, books and other documents whose authenticity can be verified. The results of the research reveal that dolanan is starting to be rarely seen and even the existence of "dolanan" is decreasing and starting to be abandoned, especially in urban areas that have touched western culture. This is also due to the current learning system which has the smell of modern and contemporary technology. Therefore, efforts are needed to refresh or reintroduce the traditional Balinese game dolanan, whose existence needs to be maintained so that it is not eroded by the times that are starting to be touched by modern culture. Training on the art of dolanan in schools is important to carry out, especially in schools which are in urban areas where if you look at the large number of children who often communicate using Indonesian rather than Balinese. Re-introducing young children to the existence of the traditional dolanan game is very important carried out as an effort to develop aspects of art in early childhood.